Antigen-specific immunosuppression in human malaria due to Plasmodium falciparum. - Ho, M; Webster, H; Looareesuwan, S; Supanaranond, W; Phillips, R; Chanthavanich, P; Warrell, D (1986)
Proliferative responses of T lymphocytes to antigens specific and not specific for malaria were investigated in 32 adult patients in eastern Thailand during acute infection with Plasmodium falciparum malaria and during their convalescence. Immune unresponsiveness to malarial antigen, which persisted for more than four weeks in 37.5% of the individuals, was present in all patients, irrespective of parasitemia or severity of clinical illness. Suppression of responses to nonspecific antigens was less profound and observed only in patients with moderately severe or cerebral malaria. The depressed functional responses were associated with a loss of T lymphocytes--both helper and suppressor subsets--from the peripheral blood; these responses were recovered once parasites were cleared. These results indicate that blood-stage plasmodial infections may suppress responses important for immunity to malaria and so allow the parasite to survive. They further suggest that patients acutely or even recently infected with P. falciparum may not respond as well to a malaria vaccine as would uninfected individuals.